Intensive Systolic Blood Pressure Lowering and Kidney Disease Progression in IgA Nephropathy: A Cohort Study - Yu, Guizhen; Cheng, Jun; Jiang, Yan; Li, Heng; Li, Xiayu; Chen, Jianghua (Frontiers in Medicine, 2022)
Background Hypertension has been shown to be an important risk factor in IgA nephropathy (IgAN). The 2021 the Kidney Disease Improving Global Outcomes (KDIGO) Guideline proposes a target systolic blood pressure (SBP) of less than 120 mmHg in patients with Chronic Kidney Disease (CKD) not receiving dialysis. However, whether lowering SBP from <140– <120 mm Hg is renoprotective is unknown. This study aims to evaluate the association of SBP and the progression of IgAN, then explore whether lowering SBP from <140– <120 mm Hg is renoprotective. Methods Overall, 2,240 patients with IgAN were enrolled in this study. Cox proportional hazards models and restricted cubic splines were used to estimate the associations between SBP and kidney failure events which are defined as 50% estimated glomerular filtration rate (eGFR) decline or kidney failure. Results After a median follow-up of 30.05 months, 217 (9.69%) patients reached composite kidney failure events. The association of SBP and kidney failure events showed a linear relationship. The risk of kidney failure events was greater with higher SBP. Compared with SBP <120 mm Hg, the hazard ratio was 1.85 (1.16–2.97, p = 0.010) for SBP <140 mm Hg after adjustment for traditional risk factors. The renoprotective benefits of therapy targeting SBP <120 mm Hg from SBP <140 mm Hg was detectable within the subgroup with proteinuria >1.0 g/d, CKD 1-3a stage, but not those with proteinuria ≤ 1.0 g/d and CKD 3b-4 stage. Conclusions In patients with IgAN, SBP was independently associated with composite kidney failure events. Lowering SBP from <140– <120 mm Hg was renoprotective.